Supplier Selection For Technical Labor Procurement Using Fuzzy Analytical Hierarchy Process Approach In The Power Company - Hari Asman; Niniet Indah Arvitrida; Suparno (Universitas Muhammadiyah Sidoarjo, 2026)
Effective procurement and supplier selection processes are needed to create a low-cost and reliable supply chain. A power company is having difficulty determining a supplier of technical personnel because there was no scientific method used to weight and prioritize supplier assessment criteria. So far, decision-making has been done more subjectively, causing a mismatch between the result of supplier selection and the company’s needs. This study uses a supplier selection model with the Fuzzy Analytical Hierarchy Process (FAHP) method to calculate the weight of each criterion and sub-criterion and determine the best supplier. The criteria used in this study include Financial Capability, Performance, Similar Experience, Expert Personnel, Office at Work Location, Similar Contracts, and Price, based on the company regulations. The result of this study shows the weight of each criterion that is: Financial Capability at 0.2007, Similar Experience at 0.1887, Performance at 0.1744, Price at 0.1545, Expert Personnel at 0.1518, Office at Work Location at 0.0877, and Similar Contracts at 0.042. Evaluation of three supplier alternatives indicates that supplier X obtained the highest preference value (0.9263), followed by supplier Y (0.8448) and supplier Z (0.8338). Sensitivity analysis on bid price changes demonstrates that supplier Z is more sensitive to price reductions than supplier Y, but supplier X remains the best alternative. Overall, FAHP effectively supports objective and comprehensive supplier selection decision-making. The proposed model can improve consistency, transparency, and procurement accountability.